Pentingnya Training Needs Analysis (TNA) Untuk Perkembangan Sdm Yang Efektif: Literatur Review - Pradita, Ardila; Eliyanti Agus Mokodompit, Sofian Sofian , Safri Laembo, (STIE AMKOP, 2025)
In the face of the dynamics of an increasingly complex and competitive business environment, human resource development (HR) is a strategic aspect for the sustainability of the organization. One of the most crucial approaches in human resource development is the implementation of Training Needs Analysis (TNA), which serves to identify competency gaps between actual conditions and organizational needs. This article is a literature review that discusses the importance of TNA in designing effective training, the methods used, and the impact of its application on organizational performance. The results of the study show that TNA carried out systematically and data-based is able to increase the relevance of training, resource allocation efficiency, and support long-term human resource development strategies. Collaborative approaches and the use of information technology have been proven to strengthen the accuracy of training needs analysis and encourage more active employee engagement. Thus, TNA is not only an administrative instrument, but a strategic foundation in organizational learning management. Kata kunci : Training Needs Analysis, human resource development, competencies, training, organizational strategy, technology.